Kepemimpinan Instruksional Kepala Sekolah dalam Meningkatkan Efektivitas Pembelajaran - Dwiyono, Yudo; Warman, Warman; Kurniawan, Dydik; Atmaja, A. A. Bagus Surya; Lorensius, Lorensius (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The study of the role of the principal's instructional leadership in the learning process is a critical factor in increasing the effectiveness of learning. This study aims to investigate the role of school principals' instructional leadership in increasing the effectiveness of learning in Samarinda Public Middle Schools, with a focus on how school principals formulate and communicate the vision, mission, and goals of the school, plan and coordinate curriculum, and carry out instructional supervision in increasing learning effectiveness. This study used a qualitative interview design involving eight participants: two teachers, three vice principals, two school committee members, and one school principal. Interview data were analyzed interactively and thematically. The results of this study indicate that the principal's strategy is to formulate the school's vision, mission, and goals together with teachers, school committees, and stakeholders. The active involvement of all stakeholders is one of the keys to realizing the school's vision and mission. The principal encourages teachers' creative efforts in learning so that learning constraints are in the classroom. Efforts to develop and improve teacher quality and transparent and objective evaluation are necessary, and evaluation is the final activity of management processes and actions. The obstacles faced were that teachers could not use interactive with students freely, the delivery of student character was partially not fulfilled, counselling guidance was not optimal, and extracurricular activities were not optimal. Efforts that have been made to overcome these obstacles are to maintain students' enthusiasm always to be active in learning, solicit learning feedback from students, and evaluate together.